The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/jof8080877
|View full text |Cite
|
Sign up to set email alerts
|

Polyphasic Systematics of the Fungicolous Genus Cladobotryum Based on Morphological, Molecular and Metabolomics Data

Abstract: (1) Background: Species of the anamorphic genus, Cladobotryum, are known for their fungicolous lifestyle, making them important mycopathogens in fungiculture. Many morphological, ecological, and molecular phylogenetic studies of the genus have been done to date, but taxonomic uncertainties and challenges still remain. Fungal secondary metabolites, being vastly diverse, are utilised as an extra tool in fungal systematics. Despite being studied for their potentially bioactive compounds, Cladobotryum species are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 88 publications
(143 reference statements)
1
6
0
Order By: Relevance
“…2c ). This positioning is also supported by other single locus-based phylogenetic analyses, in which the ITS was mainly used ( Põldmaa 2011 ; Milic et al . 2022 ).…”
Section: Resultssupporting
confidence: 73%
See 4 more Smart Citations
“…2c ). This positioning is also supported by other single locus-based phylogenetic analyses, in which the ITS was mainly used ( Põldmaa 2011 ; Milic et al . 2022 ).…”
Section: Resultssupporting
confidence: 73%
“…1937 ). The presence of aurofusarin's BGC was expected in C. mycophilum strain ATHUM6906, since a previous work in genus Cladobotryum showed that C. mycophilum is basal to the monophyletic clade formed by species producing this metabolite ( Milic et al . 2022 ).…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations